Gelatin encapsulation of chloropicrin and 1,3-dichloropropene as fumigants for soilborne diseases in the greenhouse cultivation of cucumber and tomato - Dong-dong YAN; Qiu-xia WANG; Yuan LI; Can-bin OUYANG; Mei-xia GUO; Jim Xinpei Huang; John Busacca; Jong Neng Shieh; Alisa Ye Yu; Phil Howard; Don Williams; CAO Ao-cheng (Journal of Integrative Agriculture, 2017)
Abstract: Combined use of chloropicrin (Pic) and 1,3-dicloropropene (1,3-D) is as effective as methyl bromide (MB) at controlling soilborne diseases in many trials and commercial uses. However, Pic and 1,3-D are both highly volatile and may pose strong exposure risks to humans and the environment. A gelatin capsule formulation containing Pic and 1,3-D has been developed to reduce exposure risks to workers and bystanders and improved application safety. We conducted two experiments in tomato and cucumber greenhouses located in Beijing and Qingdao, China, to study the efficacy of Pic plus 1,3-D gelatin capsules applied at different dosages and soil depths. Results indicated that both injection and gelatin capsules of Pic plus 1,3-D provided good control of soil nematodes and reduced disease index of Fusarium wilt and root-knot nematode. Plant yield of tomato and cucumber treated with gelatin capsules was similar to MB treatment. Based on our results, gelatin capsules applied at a soil depth of 15 cm provided better control of soilborne diseases and led to higher fruit yield compared to an application depth of 5 cm. In conclusion, a gelatin capsule of Pic plus 1,3-D is a promising and novel formulation, which not only shows good efficacy in controlling soilborne diseases, but also reduces potential exposure risks of fumigants.